2022
DOI: 10.1111/1556-4029.15083
|View full text |Cite
|
Sign up to set email alerts
|

A case of fatal fulminant fat embolism syndrome following multiple fractures resulting from a fall

Abstract: Fat embolism syndrome is a life‐threatening condition in which fatty substances enter the circulation and cause respiratory distress and neurological symptoms. It can occur following trauma and severe fat embolism occurring soon after trauma is known as fulminant fat embolism syndrome. Although fat staining of the lungs is helpful for diagnosing fat embolism syndrome at autopsy, clinical and other information is needed to determine the relationship between cause of death and the syndrome. In this report, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Among the reported fulminant FES cases, seven cases [13][14][15][16][17][18], including our case, were identified that developed less than 3 h after injury, with our case being the earliest after injury (Table 2). Most of the fulminant FES cases were severely ill. Another possible mechanism for cerebral fat embolization is that pulmonary fat embolization increases right atrial pressure, causing the leftover patent foramen ovale (PFO) to open, resulting in a right-to-left shunt, which allows fat droplets to flow into the arterial side and cause cerebral infarction [19].…”
Section: Discussionmentioning
confidence: 73%
“…Among the reported fulminant FES cases, seven cases [13][14][15][16][17][18], including our case, were identified that developed less than 3 h after injury, with our case being the earliest after injury (Table 2). Most of the fulminant FES cases were severely ill. Another possible mechanism for cerebral fat embolization is that pulmonary fat embolization increases right atrial pressure, causing the leftover patent foramen ovale (PFO) to open, resulting in a right-to-left shunt, which allows fat droplets to flow into the arterial side and cause cerebral infarction [19].…”
Section: Discussionmentioning
confidence: 73%
“…3 Chylous blood should not be used for clinical purposes. 4 Its injection into the patients causes adverse reactions, such as allergy, fever, and fat embolism, 5 thereby further harming the patient. Therefore, a convenient and fast method for differentiating between chylous and normal healthy blood should be urgently developed.…”
Section: Introductionmentioning
confidence: 99%